Design and Implementation of Temperature Controller for a Vacuum Distiller - M. Aziz Muslim; Goegoes Dwi N.; Ahmad Salmi F.; Akhbar Prachaessardhi R. (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
This paper proposed design and implementation of temperature controller for a vacuum distiller. The distiller is aimed to provide distillation process of bioethanol in nearly vacuum condition. Due to varying vacuum pressure, temperature have to be controlled by manipulating AC voltage to heating elements. Two arduino based control strategies have been implemented, PID control and Fuzzy Logic control. Control command from the controller was translated to AC drive using TRIAC based dimmer circuit. Experimental results show that fuzzy logic controllers have better performance in controlling temperature of vacuum distiller